Next‐generation sequencing to dissect hereditary nephrotic syndrome in mice identifies a hypomorphic mutation in Lamb2 and models Pierson's syndrome. Issue 1 (6th February 2014) - Bull, Katherine R; Mason, Thomas; Rimmer, Andrew J; Crockford, Tanya L; Silver, Karlee L; Bouriez‐Jones, Tiphaine; Hough, Tertius A; Chaudhry, Shirine; Roberts, Ian SD; Goodnow, Christopher C; Cornall, Richard J
Abstract The study of mutations causing the steroid‐resistant nephrotic syndrome in children has greatly advanced our understanding of the kidney filtration barrier. In particular, these genetic variants have illuminated the roles of the podocyte, glomerular basement membrane and endothelial cell in glomerular filtration. However, in a significant number of familial and early onset cases, an underlying mutation cannot be identified, indicating that there are likely to be multiple unknown genes with roles in glomerular permeability. We now show how the combination of N‐ethyl‐N‐nitrosourea mutagenesis and next‐generation sequencing could be used to identify the range of mutations affecting these pathways. Using this approach, we isolated a novel mouse strain with a viable nephrotic phenotype and used whole‐genome sequencing to isolate a causative hypomorphic mutation in Lamb2. This discovery generated a model for one part of the spectrum of human Pierson's syndrome and provides a powerful proof of principle for accelerating gene discovery and improving our understanding of inherited forms of renal disease. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd